THE ORIGIN OF THE "DOIRA" INSTRUMENT - Eshboyev G’ayrat Shavkat o’g’li (Sciental Journals Publishing, 2025)
The history of the emergence of national musical instruments dates back to ancient times. In the art of music, percussion instruments were among the first to appear. These include the nagora (drum), childirma, small davul, and doira. The doira instrument, which has been passed down from ancient times to the present day, has remained virtually unchanged.
Keywords: Doira, Dapp, Dapchi, Childirma, History of the Doira.